Biopsychosocial Profiles and Functional Correlates in Older Adults with Chronic Low Back Pain: A Preliminary Study. Issue 7 (16th April 2018) - Weiner, Debra K; Gentili, Angela; Coffey-Vega, Katherine; Morone, Natalia; Rossi, Michelle; Perera, Subashan
Abstract : In this cross-sectional pilot study of 47 older Veterans with chronic low back pain, central nervous system conditions (anxiety, depression, insomnia, fibromyalgia, maladaptive coping) and sacroiliac joint pain predicted self-reported disability (Roland Morris questionnaire). Maladaptive coping and fibromyalgia predicted pain intensity. Depression/anxiety and leg length discrepancy predicted gait speed, the gold standard measure of future morbidity and mortality risk in older adults. Abstract: Objective: To describe key peripheral and central nervous system (CNS) conditions in a group of older adults with chronic low back pain (CLBP) and their association with pain severity and self-reported and performance-based physical function. Design: Cross-sectional. Setting: Outpatient VA clinics. Subjects: Forty-seven community-dwelling veterans with CLBP (age 68.0 ± 6.5 years, range = 60–88 years, 12.8% female, 66% white) participated. Methods: Data were collected on peripheral pain generators—body mass index, American College of Rheumatology hip osteoarthritis criteria, neurogenic claudication (i.e., spinal stenosis), sacroiliac joint (SIJ) pain, myofascial pain, leg length discrepancy (LLD), and iliotibial band pain; and CNS pain generators—anxiety (GAD-7), depression (PHQ-9), insomnia (Insomnia Severity Index), maladaptive coping (Fear Avoidance Beliefs Questionnaire, Cognitive Strategies Questionnaire), and fibromyalgia (fibromyalgia survey). Outcomes were pain severity (0 to 10 scale, seven-day average and worst), self-reported pain interference (Roland Morris [RM] questionnaire), and gait speed. Results: Approximately 96% had at least one peripheral CLBP contributor, 83% had at least one CNS contributor, and 80.9% had both peripheral and CNS contributors. Of the peripheral conditions, only SIJ pain and LLD were associated with outcomes. All of the CNS conditions and SIJ pain were related to RM score. Only depression/anxiety and LLD were associated with gait speed. Conclusions: In this sample of older veterans, CLBP was a multifaceted condition. Both CNS and peripheral conditions were associated with self-reported and performance-based function. Additional investigation is required to determine the impact of treating these conditions on patient outcomes and health care utilization.